Nanjido: a Wasteland restoration into World Cup Park. - Kulwant Singh (2009)
Nanjido, an island in Republic of South Korea, at the end of the Han River was made a landfill site in 1978. Fifteen years later, the site had to be closed due to the extensive damage caused by the pollution of soil, air, surface and underground water created by the non-sanitary site. In 1996, the Seoul Metropolitan Government decided to undertake a major initiative to undo the damage in the area. The project is expected to continue till 2020. The task to create a World Cup Park on Nanjido Island has also addressed the issue of land use management. The goals of this major initiative have been mainly to restore the ecosystems of the once-beautiful island of Nanjido by turning the barren land into an environment-friendly eco-park. The project’s key management concept is that strong local government commitment and significant financial resources can transform a damaged environment into a recreation area for citizens. Nanjido today attracts 7-9 million tourists every year. This paper looks at the colossal damage done by the non-scientific landfilling of the site and how much can be retrieved and repaired through technological interventions. The Nanjido project has several lessons which can be learnt by the cities of the developing world.